2015
DOI: 10.1002/sm2.54
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Traumatic Penile Amputation: A Case Report and Review of the World Literature

Abstract: IntroductionThere is paucity of case reports that describe the successful reimplantation of a penis after amputation. We sought to report on self-inflicted penile amputation and comment on its surgical management and review current literature.AimTo report on self-inflicted penile amputation and comment on its surgical management and review current literature.MethodsA 19-year-old male with no prior medical history presented to our university-affiliated trauma center following sustaining a self-inflicted amputat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 15 publications
0
37
0
Order By: Relevance
“…Jezior et al reported that meticulous anastomosis of cavernosal arteries and dorsal structure was associated with erectile function 16 . A contemporary report recognized the role of microsurgical revascularization in maintaining early and adequate penile blood flow in order to achieve the best appearance and erectile and voiding function outcomes 11 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jezior et al reported that meticulous anastomosis of cavernosal arteries and dorsal structure was associated with erectile function 16 . A contemporary report recognized the role of microsurgical revascularization in maintaining early and adequate penile blood flow in order to achieve the best appearance and erectile and voiding function outcomes 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Another successful non-microscopic penile replantation was reported by Mensah et al The aforementioned case reported good voiding flow, cosmetics, and ability of penile erection. They stated name a few, the duration of ischemia time, type and mechanism of injury, severity of injury, as well as microscope use at time of surgery 5,11 .…”
Section: Discussionmentioning
confidence: 99%
“…16,17 While most literature focusing on small case series, small meta-analyses have suggested that the best outcomes are achieved with decreased ischemia time and a microsurgical approach. 18 Ischemia time should be <16 hours, replantation should focus on a watertight urethral anastomosis, and the neurovascular anastomosis should preferably be done with a microsurgical approach. 16,18,19 In the presented case, the surgery was completed <12 hours after the injury.…”
Section: Discussionmentioning
confidence: 99%
“…18 Ischemia time should be <16 hours, replantation should focus on a watertight urethral anastomosis, and the neurovascular anastomosis should preferably be done with a microsurgical approach. 16,18,19 In the presented case, the surgery was completed <12 hours after the injury.…”
Section: Discussionmentioning
confidence: 99%
“…Use of multiple options as in the index case may be tried in selected patients. If removal of the strangulating object is not possible by any of the methods because of the size of the object and/or an extreme degree of oedema, the penis may be denuded and postoperatively is treated with the same principles of severe traumatic penile and scrotal avulsion, including skin grafting or using a myo-fascial flap [9,10].…”
Section: Discussionmentioning
confidence: 99%